Predicting Waiting Time in Public Service Qeues Using Participative and GPS Sensing with Smartphones - Moraes, Adriano D.; Freitas, Allan E. S.; Marques Neto, Manoel C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Mobile computing provides new ways to help people in daily routine through ubiquituos, collaborative and social computing. Herein, we combine collaboration with ubiquitous and pervasive sensing to provide a service that helps on prediting waiting time in service queues. We argue that combining GPS information with collaboration can improve queue waiting time prediction. Our experimental evaluation uses an actual minimarket service queue, achieving a mean error of 59.56 seconds for predicting queue time in queues with observed waiting time from 120 to 240 seconds. Our results show that this tool could be useful and can be extended for other different classes of service queues.